The Effect of Concentration and Work Stress on Employee Work Productivity - Dharasta, You She Melly Anne; Utami, Shely Budi (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Work productivity is a benchmark for a company in achieving its goals. One important element in an organization or company is human resources. This research was conducted at the Airport Operation Landside & Terminal (AOLT) Unit at Yogyakarta International Airport. The aim of this research is to determine the influence of concentration and work stress on employee work productivity and to find out how much influence the independent variables, namely concentration and work stress, have on the dependent variable, namely work productivity. This research uses quantitative research methods with data collection techniques using questionnaires distributed to employees of the Airport Operation Landside & Terminal unit. The data collection technique uses a questionnaire distributed to respondents. The results show that concentration and work stress each have a significance value of 0.038 on work productivity. Then, the F Test results show that concentration and work stress have a significance value of 5.085. The coefficient of determination test shows that concentration and work stress have a 33.8% influence on work productivity.